Association between fluid overload and mortality in children with sepsis: a systematic review and meta-analysis - Jaime Fernández-Sarmiento; Marco Fidel Sierra-Zuñiga; María Paula Salazar González; Natalia Lucena; Vanessa Soares Lanziotti; Sergio Agudelo (BMJ Publishing Group, 2023)
Background Sepsis is one of the main causes of morbidity and mortality worldwide. Fluid resuscitation is among the most common interventions and is associated with fluid overload (FO) in some patients. The objective of this systematic review and meta-analysis was to summarise the available evidence on the association between FO and morbimortality in children with sepsis.Methods A systematic search was carried out in PubMed/Medline, Embase, Cochrane and Google Scholar up to December 2022 (PROSPERO 408148), including studies in children with sepsis which reported more than 10% FO 24 hours after admission to intensive care. The risk of bias was assessed using the Newcastle-Ottawa scale. Heterogeneity was assessed using I2, considering it absent if <25% and high if >75%. A sensitivity analysis was run to explore the impact of the methodological quality on the size of the effect. Mantel-Haenszel's model of random effects was used for the analysis. The primary outcome was to determine the risk of mortality associated with FO and the secondary outcomes were the need for mechanical ventilation (MV), multiple organ dysfunction syndrome (MODS) and length of hospital stay associated with FO.Results A total of 9 studies (2312 patients) were included, all of which were observational. Children with FO had a higher mortality than patients without overload (46% vs 26%; OR 5.06; 95% CI 1.77 to 14.48; p<0.01). We found no association between %FO and the risk of MODS (OR: 0.97; 95% CI 0.13 to 7.12; p=0.98). Children with FO required MV more often (83% vs 47%; OR: 4.78; 95% CI 2.51 to 9.11; p<0.01) and had a longer hospital stay (8 days (RIQ 6.5-13.2) vs 7 days (RIQ 6.1-11.5); p<0.01).Conclusion In children with sepsis, more than 10% FO 24 hours after intensive care admission is associated with higher mortality, the need for MV and length of hospital stay.